Beaches in Space and Time : a Global Look at the Beach Environment and How We Use It. - Davis, Richard A. (Pineapple Press, 2015)
Learn how beaches originate, what they are made of, and how wind, waves, tides, storms, sea-level changes, and human development affect them in this beautiful book that has nearly 200 illustrations.